Study on the occurrence and morphology of Hungarian Thymus species - Simkó, Hella; Sárosi, Szilvia Z.; Reményi, Mária Lujza; Pluhár, Zsuzsanna (JOURNAL OF LANDSCAPE ECOLOGY, 2012)
Hybridization ability and high variability of Thymus species in natural habitats is a well-known phenomenon. In certain populations not only different chemotypes can be found, but diverse morphological features as well. Our results were in accordance with previous data concerning native Thymus pannonicus, T. glabrescens and T. pulegioides populations of the Hungarian Flora. Thymus pannonicus and T. glabrescens are generalist species with pioneer character, occurring also on ruderal habitats and tolerating wide range of parent rocks and soil types. We examined their samples originating from various habitats of the Hungarian Mountain Range (Bakony Hills, Balaton Uplands, Somogy Hills, Velence Hills, Vértes Hills, Gerecse Hills, Pilis Hills, Buda Hills, Visegrád Hills, Gödöllő Hills, Bükk Mountains, Mátra Mountains, Cserehát, and Zemplén Mountains). Chemotaxa possessing lemon scent was found to be frequent at Thymus pulegioides, but also exists in the populations of T. pannonicus, which was new for the literature (SIMON 2000). According to the examined herbarium specimen, Thymus glabrescens and T. pannnonicus samples showed the greatest morphological variability among the five native Hungarian Thymus species. Thymus pannonicus samples had values of 1.25−7.00 for leaf length/leaf width ratio, which means its leaf shape is the most heterogeneous of all species, while in most cases they possessed lanceolate leaves. As for the flower colour, they can bloom in those shades which were unknown before. To complement the data about shoot covering trichomes of Thymus pulegioides, all the three types have been observed: goniotrichous (on the angles only), alelotrichous (on two sides alternating on each internode) and holotrichous (on all sides), respectively. The whole shoots were covered by leaves at T. glabrescens and T. pulegioides, while in the case of T. pannonicus leaf density was higher at the upper part of the stem. The leaf density was medium or high at Thymus pannonicus and T. glabrescens, while at T. pulegioides was rare in the majority of the samples. At Thymus pannonicus samples, the stem was densely coated with covering hairs in the inflorescence, between the whorls, while in the case of the other two species this feature was not so frequent. However the last descriptor has not been recommended to use for taxonomical differentiation, because covering hair development depends mainly on the habitat and the environmental conditions (DAjIć-STEVANOVIć et al. 2004).